Characterisation of damage due to abrasion in SCC by acoustic emission analysis. Issue 2 (2nd March 2018) - Ridgley, Katherine E.; Abouhussien, Ahmed A.; Hassan, Assem A. A.; Colbourne, Bruce
Abstract : This investigation evaluates and compares the abrasion resistance of various concrete types by means of acoustic emission (AE) analysis. Normal concrete, self-consolidating concrete (SCC) and SCC with variable supplementary cementing materials (SCMs) were tested under the rotating cutter method for abrasion resistance. The effect of using different SCMs in SCC mixtures including fly ash, metakaolin (MK), silica fume and slag on the abrasion resistance of SCC was examined. In conjunction with the abrasion testing, AE monitoring was simultaneously conducted on all mixtures using AE attached sensors. AE parameters such as signal amplitude, signal strength, number of hits, duration and cumulative signal strength (CSS) were collected during the abrasion tests. Three additional parameters were determined through further analyses: b -value, severity ( S r ) and historic index ( H ( t )). Results from the abrasion tests indicated that the SCC mixture containing MK had the highest abrasion resistance among all tested mixtures. The studied AE parameters including CSS, number of hits, b -value, H ( t ) and S r were well correlated to the extent of abrasion damage in all tested specimens. The progression of abrasion damage was associated with increased AE activities indicated by high fluctuations in the b -value and H ( t ) along with ever-increasing values of CSS, number of hits and S r . The AE intensity analysis quantified which ranges for H ( t ) and S r would indicate the extent and severity of the damage due to abrasion by means of developed damage classification charts.